2009
DOI: 10.1021/ja8088923
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the Δ10,1211,13 Double Bond Migration During Ansamitocin Biosynthesis in Actinosynnema pretiosum

Abstract: The timing of introduction of the unusually placed Delta(11,13) diene system in ansamitocin (AP) biosynthesis was probed by synthesizing optically active potential tri- and tetraketide intermediates as their SNAC thioesters. An AP-nonproducing mutant Actinosynnema pretiosum was complemented by the R enantiomer of the triketide and by the tetraketide with rearranged double bonds, but not by the tetraketide carrying the double bonds in conjugation to the thioester function. The results show that the double bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 20 publications
4
47
0
2
Order By: Relevance
“…Likewise, the double bonds D 25, 27 and D 11, 12 appear to have changed position relative to their locations in regular PKS/NRPS systems, although exceptions to this have recently been described. [21][22][23][24] Analysis of the corallopyronin A biosynthetic gene cluster Feeding experiments showed that the core structure of corallopyronin A is the product of a mixed PKS/NRPS biosynthetic machinery. Investigations with 13 C-labelled SAM, as well as the positions of the corresponding methyl functionalities (i.e., aor b-branching or ÀOCH 3 ) in the molecule, clearly showed that methyl and methoxy groups are incorporated by two mechanisms: from SAM dependent by MTs and by the successive action of a b-branching cassette.…”
Section: Wwwchembiochemorgmentioning
confidence: 99%
“…Likewise, the double bonds D 25, 27 and D 11, 12 appear to have changed position relative to their locations in regular PKS/NRPS systems, although exceptions to this have recently been described. [21][22][23][24] Analysis of the corallopyronin A biosynthetic gene cluster Feeding experiments showed that the core structure of corallopyronin A is the product of a mixed PKS/NRPS biosynthetic machinery. Investigations with 13 C-labelled SAM, as well as the positions of the corresponding methyl functionalities (i.e., aor b-branching or ÀOCH 3 ) in the molecule, clearly showed that methyl and methoxy groups are incorporated by two mechanisms: from SAM dependent by MTs and by the successive action of a b-branching cassette.…”
Section: Wwwchembiochemorgmentioning
confidence: 99%
“…One is 4,5-C=C moiety in geldanamcyin [8], in which the ER domain in module 6 is apparently functional. Another is that, even though asm DH3 seemed functional, 10,12 double bond migrates to 11,13 in ansamitocin P3 [88]. Despite some shortcomings that can not be overcome in near future, the actually elucidated structures will not deviate too far from the predicted ones.…”
Section: Non-colinearitymentioning
confidence: 95%
“…Key steps are the introduction of the stereogenic center at C-14 by an Evans alkylation and a phosphonate-based olefination using α-methoxy SNAC ester 68. 41 We demonstrated that mutasynthesis is ideally suited to the synthesis of highly potent ansamitocins, making it a showcase for combining the use of different blocked mutants with chemical synthesis. Several hybrid concepts were tested and allowed a large number of analogues of this class of structurally complex secondary metabolites to be generated.…”
Section: Blocked Mutants As Tools For Biosynthetic Studies Of Ansamitmentioning
confidence: 99%